Old style : unoriginality and its uses in nineteenth-century U.S. literature - Stokes, Claudia, 1970- (University of Pennsylvania Press, 2022)
"We celebrate innovation and experimentation, but Old Style reminds us that nineteenth-century American writers instead valued familiarity and traditionalism, which provided reliable markers of literary quality. Old Style examines the varied uses and expressions of unoriginality, which helped credential marginalized writers but which would eventually become associated with elitist conservatism"--